Exploring Green Tax Through A Systematic Literature Review: Analyzing Developments In Promoting Sustainability - Prasetyawati, Tyas; Imelda, Imelda; Fuadah, Luk Luk (Jurnal Fokus Manajemen, 2025)
This study aims to explore various aspects related to green tax by employing a Systematic Literature Review (SLR) approach, analyzing 24 previous research articles. The literature sources were collected from several reputable scientific databases such as Scopus, Emerald, and DOAJ, covering publications from 2015 to 2025. Green tax is identified as a policy instrument designed to encourage environmentally friendly behavior and to internalize the external costs arising from environmentally damaging activities. Although green tax holds significant potential in supporting sustainability efforts, its implementation often faces various challenges, including the public’s limited understanding of the importance of environmental sustainability. The analysis results show an increase in the number of publications on green tax during the period, reflecting growing attention from researchers and academics toward this issue. Moreover, energy efficiency was identified as a key factor mediating the relationship between the application of green tax and the achievement of sustainability performance. The findings affirm that environmental taxation has considerable potential to serve as an effective tool in promoting sustainable development both in Indonesia and other countries. Policy recommendations include combining green tax strategies with consumer subsidies, along with efforts to enhance public awareness regarding the importance of environmental protection and sustainability